Essencialidade e peculiaridades do serviço público registral e notarial - Felisberto, Bruno Miguel Costa (2013)
This essay is about to discuss the essentiality and the peculiarities of the public service developed by the notaries and registrars in Brazil. For this, it will be done, by first, a historical incursion showing the beginning of the activities, its development due to the current model, its nature and the sources correlative to it. Some controversial themes will be discussed, such as the admission and permanence in the activity without any previous public contest, reporting cases still existing on the present days, analyzing the necessary attitudes in order to repel this scenario. It will be also shown the importance of this public service and its relevance due to society, analyzing, as well, the brazilian system in comparison to other countries. In sequence, it will be discussed the matter of civil liability related to the notaries and registrars, evaluating which theory applies to it: objective or subjective. By the end, there is a study about the controversy related to the discussion that questions if the consumer protection code is applied to the notaries and registrars service.